An Islanded DC Microgrid Blueprint for Residential Applications - Maurya, Rinki; Nishad, Dashrath; Srivastava, Ankit; Rai, Chandravilash; Prakash, Surya; Singh, Ashutosh Kumar (International Conference on Electrical and Electronics Engineering, 2024)
Rising energy demands and unsustainable practices necessitate innovative solutions. Motivated by a middle-class family's requirements, the system makes use of solar energy that is efficiently handled via a DC-DC converter and harvested by photovoltaic panels. This paper presents the design of an island DC microgrid specifically tailored for residential applications. A battery storage system with optimized charging and discharging capabilities ensures power availability, even during grid outages. Stable voltage regulation within the microgrid is achieved through a current-controlled PID controller. The system incorporates a mix of constant power loads to optimize energy utilization. This detailed design offers a sustainable and reliable residential power solution, paving the way for wider adoption of DC microgrids and a greener future.